Jakarta's Readiness for the Waste Reduction Program at the Source - Nurfadhillah Ummamah; Dwi Nowo Martono; Kurniawaty Iskandar (Jurnal Penelitian Pendidikan IPA, 2024)
DKI Jakarta as the capital of Indonesia has a policy to manage waste (recycling) in a decentralized manner, namely that waste is managed as close as possible to its source, without relying on disposal in landfills anymore. This pro-environment policy targets reducing and handling waste by 30% and 70% respectively by 2030. Currently the program is being implemented, non-residual waste will be processed and recycled in decentralized processing or TPS 3R. In order to achieve this target, the community and government must work together to make changes and must have a sense of ownership, responsiveness, concern and responsibility for the waste produced. This research uses a qualitative approach with observations, questionnaires to 330 respondents and interviews with the community and local government. And this research found that TPS and TP3R public facilities still do not comply with existing regulations and do not meet the criteria for accommodating recycling activities. From 2018-2022, the reduction in waste generation was 9% from the target of 26% and the amount of waste handling was 1.66% from the target of 70%. People still don't recycle for various reasons and there is also a lack of consistency in implementing recycling behaviour due to rational attitudes such as just paying money for waste. The government is obliged to facilitate these recycling activities together with various stakeholders, by carrying out various innovations and outreach to the community, by implementing waste management based on community participation.